If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2x + 1) + -2(5x + 2) = 0 Reorder the terms: 6(1 + 2x) + -2(5x + 2) = 0 (1 * 6 + 2x * 6) + -2(5x + 2) = 0 (6 + 12x) + -2(5x + 2) = 0 Reorder the terms: 6 + 12x + -2(2 + 5x) = 0 6 + 12x + (2 * -2 + 5x * -2) = 0 6 + 12x + (-4 + -10x) = 0 Reorder the terms: 6 + -4 + 12x + -10x = 0 Combine like terms: 6 + -4 = 2 2 + 12x + -10x = 0 Combine like terms: 12x + -10x = 2x 2 + 2x = 0 Solving 2 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 2x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 2x = 0 + -2 2x = 0 + -2 Combine like terms: 0 + -2 = -2 2x = -2 Divide each side by '2'. x = -1 Simplifying x = -1
| 1.7x-3=-1.3 | | 120.80=3.20+57.20 | | 2sin^3x-sin^2x-2sinx-1=0 | | n-6n+8=0 | | 2sin^3x+sin^2x-2sinx+1=0 | | x^10=74 | | 9x-68=52-x | | (k+2)=16 | | 3(j+4)=35 | | 2a^2-2a+99=0 | | 5x^2-4x-460=0 | | 6(5-2x)-8=106 | | -5x-96=-10x+34 | | 5x^2-4x-461=0 | | 24-49x-6-9x=2-30x | | (m-2)=5 | | 3y-12x+6=o | | 25x-4=3x^2+8x+16 | | -1x+-5=25 | | -7-k=7-3k | | 3y=6+6x | | 16+6=x-70 | | 12-3y=14 | | -294-(-70)= | | 10x+70+7x=13+x | | (m-7)=49 | | -1+-5=25 | | -4y+4(4y+4)=8+6(8-y) | | 12x-69=3x+102 | | -.666x(6-3z-7)= | | 23x-3y=5 | | 7-2(x-3)=5-8 |